Educational services export: competition in new geopolitical conditions - E. N. Bykovskaya; M. N. Rybina (Вестник университета)
Geopolitical tensions are on the rise. The competitive struggle in the field of educational services export does not stand aside either. In a fierce confrontation, a rich arsenal of modern technologies is used. Using the information onslaught, the ideology, the mentality of the younger generation, its worldview positions become the goal of this struggle. Russia has always been a competitive country in the export of educational services. However, in today’s conditions of fierce competition, it is necessary to defend one’s positions, find advantages in the Russian educational system, relying both on accumulated experience and using innovative approaches. In order to be competitive in the modern world community, during the transition to a new technological order, it is necessary to offer innovative products in the field of education, expand the range of the subjects of the educational environment on various regional platforms.